Association of baseline Life’s Essential 8 score and trajectories with carotid intima-media thickness - Liu, Qian; Cui, Haozhe; Chen, Shuohua; Zhang, Dongyan; Huang, Wei; Wu, Shouling (Frontiers in Endocrinology, 2023)
Objective: We aimed to examine the association of baseline Life’s Essential 8 (LE8) score and LE8 score trajectories with the continuous carotid intima-media thickness (cIMT) and risk of high cIMT. Methods: Participants who completed the first physical examination in the Kailuan study and cIMT detection at follow-up were included. Participants were categorized into five groups (Q1, Q2, Q3, Q4, and Q5) according to quintiles of baseline LE8 score, and into four groups according to LE8 score trajectories. In addition to the continuous cIMT measurement, an age- (5 years), and sex-specific 90th percentile cut point determined high cIMT. To address aim 1 and 2, the association between baseline/trajectory groups and continuous cIMT/high cIMT was assessed by using SAS proc genmod to calculate β, relative risk (RR), and 95%confidence intervals (CI). Results: A total of 12,980 participants were finally included in aim 1, and 8,758 participants met aim 2 of association between LE8 trajectories and cIMT/high cIMT. Compared with the Q1 group, the continuous cIMT for Q2, Q3, Q4, and Q5 group were thinner, the other groups had lower risk of high cIMT. Results of aim 2 showed: compared with very low-stable group, the cIMT for low-stable, median-stable group, and high-stable group were thinner (-0.07mm [95%CI -0.10 0.04mm], -0.10mm [95%CI -0.13 -0.07mm], -0.12mm [95%CI -0.16 -0.09mm]), the other groups had lower risk of high cIMT, the RR(95%CI) for high cIMT were 0.81 (0.73 0.90) in low-stable group, 0.61 (0.54 0.68) in median-stable group, 0.43 (0.35 0.54) in high-stable group. Conclusions: High baseline LE8 score and LE8 score trajectories were associated with lower continuous cIMT and attenuated risk of high cIMT in the study.